2019
DOI: 10.1136/gutjnl-2019-318365
|View full text |Cite
|
Sign up to set email alerts
|

Phase III, randomised, double-blind, multicentre study to evaluate the efficacy and safety of vonoprazan compared with lansoprazole in Asian patients with erosive oesophagitis

Abstract: ObjectiveTo establish the non-inferior efficacy of vonoprazan versus lansoprazole in the treatment of Asian patients with erosive oesophagitis (EO).DesignIn this phase III, double-blind, multicentre study, patients with endoscopically confirmed EO were randomised 1:1 to receive vonoprazan 20 mg or lansoprazole 30 mg, once daily for up to 8 weeks. The primary endpoint was EO healing rate at 8 weeks. The secondary endpoints were EO healing rates at 2 and 4 weeks. Safety endpoints included treatment-emergent adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
143
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(153 citation statements)
references
References 38 publications
3
143
1
6
Order By: Relevance
“…Vonoprazan, which belongs to a class of acid-inhibitory agents called potassium-competitive acid blockers, was approved in Japan in February 2015, and its superiority or non-inferiority to PPIs for the treatment of acid-related diseases has been demonstrated [45][46][47]. Although vonoprazan suppresses gastric acid secretion by a different mechanism from PPIs, a recent animal study reported that both rabeprazole and vonoprazan aggravated NSAIDs-induced small intestinal injury in mice by reducing the population of Lactobacillus johnsonii in the small intestine [48].…”
Section: Risk Factors For Nsaids-induced Enteropathymentioning
confidence: 99%
“…Vonoprazan, which belongs to a class of acid-inhibitory agents called potassium-competitive acid blockers, was approved in Japan in February 2015, and its superiority or non-inferiority to PPIs for the treatment of acid-related diseases has been demonstrated [45][46][47]. Although vonoprazan suppresses gastric acid secretion by a different mechanism from PPIs, a recent animal study reported that both rabeprazole and vonoprazan aggravated NSAIDs-induced small intestinal injury in mice by reducing the population of Lactobacillus johnsonii in the small intestine [48].…”
Section: Risk Factors For Nsaids-induced Enteropathymentioning
confidence: 99%
“…As a potential alternative to proton-pump inhibitors (PPIs), vonoprazan has been verified to be superior to conventional PPIs or even more effective in distinct gastric acid-related clinical indications. A phase III multicenter study demonstrated that there was no significant difference between vonoprazan and lansoprazole in treating erosive esophagitis (Xiao et al, 2020). In terms of preventing the recurrence of low-dose or long-term aspirin-associated ulcers, vonoprazan has proven to be as effective as lansoprazole (Kawai et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding safety, vonoprazan is well tolerated and has a similar incidence of treatment-emergent adverse events as lansoprazole (22.2%-38.1% vs. 22.3%-36.6%). 9,10 Vonoprazan users had higher serum gastrin levels than PPI users. 10,11 Hypergastrinaemia may be a potential risk for neuroendocrine tumours 12 ; nonetheless, no cases of neuroendocrine tumour caused by vonoprazan-associated hypergastrinaemia have been reported.…”
Section: Introductionmentioning
confidence: 90%